2018
DOI: 10.1002/uog.18825
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound evaluation of left ventricular and aortic fibrosis after pre‐eclampsia

Abstract: Women with a history of EO-PE show LV fibrosis in the short-medium term after delivery compared with women with previous LO-PE pregnancy and controls. LV fibrosis is associated with GA and mean UtA-PI at onset of PE. Larger studies using cardiac magnetic resonance imaging are needed to validate and confirm our findings. Copyright © 2017 ISUOG. Published by John Wiley & Sons Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…Arterial stiffness is widely considered an independent predictor of cardiovascular morbidity and it is also able to anticipate hypertension in previously normotensive women, providing additional value in cardiovascular risk‐profile definition. As highlighted previously, our findings try to provide another possible explanation for the higher risk of cardiovascular events later in life in these women than in the general female population of the same age. Currently, fibrosis is considered both a dynamic marker of cardiovascular disease severity and a determinant of future LV remodeling.…”
Section: Echocardiographic Calibrated Integrated Backscatter (Cibs) Asupporting
confidence: 63%
See 2 more Smart Citations
“…Arterial stiffness is widely considered an independent predictor of cardiovascular morbidity and it is also able to anticipate hypertension in previously normotensive women, providing additional value in cardiovascular risk‐profile definition. As highlighted previously, our findings try to provide another possible explanation for the higher risk of cardiovascular events later in life in these women than in the general female population of the same age. Currently, fibrosis is considered both a dynamic marker of cardiovascular disease severity and a determinant of future LV remodeling.…”
Section: Echocardiographic Calibrated Integrated Backscatter (Cibs) Asupporting
confidence: 63%
“…By means of integrated backscatter (IBS), we described recently the presence of left ventricular (LV) and aortic fibrosis in women with a previous pregnancy complicated by early‐ or late‐onset pre‐eclampsia (PE), finding that early‐onset PE is characterized by persistent LV fibrosis, which correlates with cardiac structural and functional abnormalities, and a non‐statistically significant trend towards aortic fibrosis. Calibrated IBS (cIBS) provides information on myocardial reflectivity of ultrasound, assessed at the interventricular septum (IVS), LV posterior wall (PW) and ascending aorta (AO), measured in decibels (dB), conventionally as negative numbers, and averaged and calibrated to the reflectivity of the pericardium. The same echocardiographic evaluation was performed in the population of two other previous studies published in this Journal, involving 49 women with a history of HELLP syndrome and 60 with a previous pregnancy complicated by PE, compared with 60 healthy controls, evaluated between 6 months and 4 years after delivery,.…”
Section: Echocardiographic Calibrated Integrated Backscatter (Cibs) Amentioning
confidence: 99%
See 1 more Smart Citation
“…us, the in vivo levels of MBG observed in patients with PE in our previous and present studies are capable of enhancing vascular tone and substantially inhibiting NKA. e mechanism of PE includes remodeling of uterine spiral arteries and making them fibrotic by a variety of vascular factors including cardiotonic steroids [20,21]. Physiological function of CS is regulation of sodium excretion by means of inhibition of NKA in the epithelial cells of renal tubuli, i.e., an adaptive response [20].…”
Section: Fibrosis and Preeclampsiamentioning
confidence: 99%
“…Consistently, we found that both components of VAC were altered in the EOPE group 48 . By means of integrated backscatter, we described the presence of LV fibrosis in the EOPE group 58 . Our results, highlighting the extent of myocardial damage from structural and functional points of view, identify one of the possible mechanisms of HF development in these women.…”
Section: Heart Failure After Pregnancy Complicated By Pre-eclampsiamentioning
confidence: 99%